Seasonal Distributions of External Myiasis Flies Determined in Diyabakir Province - Ipek, Duygu Neval Sayin; Saki, Cem Ecmel; Ozer, Edip (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
This study was carried out in Diyarbakir city center, and Silvan, Ergani, Cinar, Lice town between in January 2008 - December 2009. In order to gather the flies, then to capture and then to kill them, the odour bait traps were used. 6581 flies were caught from traps in total. The flies were identified in the laboratory according to their morphological characteristics and it was seen that 5424 (82.43%) of the flies were Lucilia sericata, 833 (12.65%) were Calliphora vicina, 222 (3.38%) Chrysomyia albiceps, 93 (1.42%) were Calliphora vomitoria, 3 (0.04%) were Sarcophaga haemorrhoidalis, 3 (0.04%) were Sarcophaga argyrostoma and 3 (0.04%) were S. sarcophaga carnaria. It was determined that 5186 (78.80%) of the total number of flies were female and 1395 (21.20%) were male. Females and males of all the species, except males of Sarcophaga argyrostoma and Sarcophaga carnaria, were detected. Flies did not appear in January, December and August in both years. The flies appeared at highest rate in April 2008 (48.43%) and in April 2009 (45.64%) respectively.
Keywords: Calliphoridae; Sarcophagidae; Diyarbakir; Seasonal Distributions